PERFORMANSI POMPA AIR DAB TYPE DB-125B YANG DIFUNGSIKAN SEBAGAI TURBIN AIR - Adi R. M. Arief; Gerits Dirk Soplanit; I Nyoman Gede (Fakultas Teknik Jurusan Teknik Mesin Universitas Sam Ratulangi, 2012)
The use of water pumps DAB type DB-125 as the impulse turbine functions for Micro Hydro Power Plant Lisrik (PLTMH) is the topic in this research. Water pump is used to suck water and deliver it to a certain height. In this application the water pumps used as turbines where water from a certain height will rotate the impeller pump and produces electricity. The testing is done in the laboratory of mechanical engineering of University of Sam Ratulangi. Turbine is driven by three pumps which are assembled in series and parallel, to get different head and flow (Q). Water flow and load on dinamometer ( ) have been set at the lowest rotation of the load on turbine. For the initial set of water flow Q = 33,5 litres/minute. The results showed that the different H and Q from curve turbine rounds, maximum power is at Q = 40 litres/minute, H = 33,5 m, and n = 910 rpm